The effect of resin uptake on the flexural properties of compression molded sandwich composites. Issue 1 (20th July 2021) - Cao, Dongyang; Malakooti, Sadeq; Kulkarni, Vijay N.; Ren, Yao; Liu, Yingjian; Nie, Xu; Qian, Dong; Griffith, D. Todd; Lu, Hongbing
Abstract: Resin uptake plays a critical role in the stiffness‐to‐weight ratio of wind turbine blades in which sandwich composites are used extensively. This work examines the flexural properties of nominally half‐inch thick sandwich composites made with polyvinyl chloride (PVC) foam cores (H60 and H80; PSC and GPC) at several resin uptakes. We found that the specific flexural strength and modulus for the H80 GPC sandwich composites increase from 82.04 to 90.70 kN · m/kg and 6.03 to 7.13 MN · m/kg, respectively, with 11.0% resin uptake reduction, which stands out among the four core sandwich composites. Considering reaching a high stiffness‐to‐weight ratio while preventing resin starvation, 32% to 38% and 40% to 45% resin uptakes are adequate ranges for the H80 PSC and GPC sandwich composites, respectively. The H60 GPC sandwich composites have lower debonding toughness than H60 PSC due to stress concentration in the smooth side skin‐core interphase region. The ailure mode of the sandwich composites depends on the core stiffness and surface texture. The H60 GPC sandwich composites exhibit core shearing and bottom skin‐core debonding failure, while the H80 GPC and PSC sandwich composites show top skin cracking and core crushing failure. The findings indicate that an appropriate range of resin uptake exists for each type of core sandwich composite, and that within the range, a low‐resin uptake leads to lighter blades and thus lower cyclic gravitational loads, beneficial for long blades.